The relationship between teacher-student interaction, and motivation and achievement in ESL classroom amongst secondary school students / Azrin Raimi Ahmad - Ahmad, Azrin Raimi (2016)
This study aimed at studying the relationship of teacher-student interaction on secondary school approach was employed in this study. A questionnaire and group interviews were used as the tools to collect data from 145 students in a selected secondary school in Kuala Terengganu. The results showed that there was a significant relationship between teacher-student interaction and students' level of motivation. However, the findings found that there were no significant relationship between teacher-student interaction and students' ESL achievement. The results also revealed that there was a relationship between students' level of motivation and ESL achievement. Educators should use the information found in this study to enhance ESL teaching and learning. Teachers can help at risk students by creating a positive teacher-student interaction as it has an impact on students' motivation.